Cosy Crime Fiction, Australian Regions and Climate Crisis: Reading Sue Williams's Rusty Bore Series in the Victorian Mallee - Potter, Emily; Magner, Brigid (Journal of the Association for the Study of Australian Literature : JASAL, 2024)
Set largely in the Victorian Mallee region, in the tiny fictional town of Rusty Bore, Williams's novels (Murder with the Lot, 2013; Dead Men Don't Order Flake, 2016; Live and Let Fry, 2018; and Death at the Belvedere, 2022) adhere to the conventions of the cosy, with its female, fish and chip shop-owning protagonist, attentive to the dynamics of her small rural town. [...]the playful use of humour and "offstage" action is blended with direct commentary on the climate crisis in the context of global capitalism and its impact on rural communities, and the exploitative, violent and corrupt structures that support this. [...]the rural setting of the novels, in an agricultural area of northwest Victoria, is harnessed by Williams to explore some of the complexities of climate action, especially in regional contexts where 28 percent of the Australian population live (Australian Institute of Health and Welfare). Part of a larger program of participatory literary events that we have run in the Mallee region, these book discussions illuminated cosy crime fiction's local, relational and humorous dimensions. The events enabled participants to reflect on their rural places and communities in relation to the themes of environmental and colonial violence and their impacts on the future of rural communities in ways that seem productive for the challenge of navigating climate crisis in regional Australia.